THE ESSENCE OF THE MANAGEMENT OF AGRICULTURAL LAND USE THROUGH THE LENS OF LAND RIGHTS: ECONOMIC AND LEGAL ASPECTS - Tretiak, A. M.; Kurilets, R. N.; Kovalyshyn, O. F. (Land Management, Cadastre and Land Monitoring, 2013)
The analysis of the nature of management of agricultural land use as a key compo‐ nent of a holistic land‐property complex in the light of land rights, studied their char‐ acteristics as part of the economic and legal relations of land ownership under the current legislation of Ukraine